Cognitive testing in early-phase clinical trials: Development of a rapid computerized test battery and application in a simulated Phase I study - Collie, Alex; Darekar, Amanda; Weissgerber, Georges; Toh, Melvin K.; Snyder, Peter J.; Maruff, Paul; Huggins, John P. (Contemporary clinical trials, 2007)
Inclusion of cognitive assessment in Phase I trials of novel pharmaceutical agents may help identify subtle yet meaningful CNS effects early in clinical development, and lead to a greater understanding of the pharmacokinetic/pharmacodynamic relationship prior to entering pivotal late-phase trials. To examine issues surrounding the inclusion of a computerised cognitive test battery in Phase I clinical trials. A 12-minute battery of five computerized cognitive tasks was administered to 28 healthy males in a double-blind, single ascending dose study using three doses of midazolam (0.6 mg, 1.75 mg and 5.25 mg) with placebo insertion. Subjects were enrolled and assessed at two Phase I units. Statistical analyses sought to determine the sensitivity of the test battery to sedation-related cognitive dysfunction, any between-site differences in outcome, and also the effects of repeated test administration (i.e., practice or learning effects). There were no significant differences in data collected between sites. All standard safety measurements were completed. No substantial technical issues were noted. No learning effects were observed on four of the five cognitive tasks. ANOVA comparing baseline to post-baseline results revealed significant cognitive deterioration on all five cognitive tasks 1 h following administration of 5.25 mg midazolam. The magnitude of these changes were very large according to conventional statistical criteria. Smaller but significant changes were observed on a subset of memory and learning tasks at 1 h post-dosing in 1.75 mg condition, and at 2 h post-dosing in the 5.25 mg condition. The cognitive test battery was well tolerated by subjects and research unit staff. The tests demonstrated minimal learning effects, were unaffected by language and cultural differences between sites, and were sensitive to the sedative effects of midazolam. Inclusion of this cognitive test battery in future studies may allow identification of cognitive impairment or enhancement early in the clinical development cycle.